Benthamov "fragment" in odkrivanje korenin sodobnosti - Novak, Aleš (Pravnik, 2015)
In this cursory presentation of the (first) Slovenian translation of Jeremy Bentham's Fragment on Government the author briefly outlines the background in which this famed pamphlet appeared and proceeds to comment briefly on four topics deserving of attention. The first is Bentham influential insistence on the fundamental difference between expository and censorial approach to law, which laid the foundation of positivist methodology. The second centres on his outline of what has become known as command theory of law and (still) attributed predominantly to John Austin. The reviewer argues that Bentham should be more widely credited as the real founding father of this theory. The third emphasises his critique of natural law, which makes Bentham one of the first fully-fledged legal positivist. The fourth tries to shed light to an obscure passage in which Bentham seems to visualise the possibility of and comments on judicial review, in particular, the court's power to strike down legislation. Finally, the review offers some observations on the Slovenian translation.
Keywords: Bentham, Jeremy, (1748-1832); Bentham, Jeremy: Fragment o vladavini; filozofija politike; ocene in poročila; teorija; theory; utilitarizem